Methodologies and standards for monitoring antimicrobial use and antimicrobial resistance in shrimp aquaculture - Devadas, S.; Zakaria, Z.; Shariff, M.; Bhassu, S.; Karim, M.; Natrah, I. (Elsevier, 2024)
Antimicrobials are commonly used to treat and prevent bacterial diseases in aquaculture. However, prolonged antimicrobial use in aquaculture leads to public health hazards by developing antimicrobial-resistant pathogens that can cause infections in humans and animals. Multiple classes of antibiotics, such as fluoroquinolones, quinolones, tetracyclines, sulfonamides as well as nitrofurans and chloramphenicol, which are banned for use in food-producing animals in most countries, have been used in shrimp farming. Hence, the aquaculture industry may play a role in global AMR dissemination due to its direct connectivity to the aquatic environment and high levels of international shrimp trade. Under these circumstances, monitoring antimicrobial use (AMU) and antimicrobial resistance (AMR) in shrimp aquaculture is critically essential for interpreting AMR data and updating on the emergence of AMR, respectively. Nevertheless, various methodologies and standards have been used to study and report the antimicrobial susceptibility of bacteria isolated from shrimp and shrimp culture environments. Furthermore, lack of publications reported data on AMU and linkages between AMU and AMR frequencies observed. Limited information on harmonized and standardized methodologies to study AMU and AMR has been a great challenge to aquaculture researchers. More information is critically required to improve our understanding and enhance ongoing research work on AMU and AMR in shrimp aquaculture in Malaysia. Hence, we decided to explore and present an overview of methodologies and standards for monitoring AMU and AMR in shrimp aquaculture. Additional information about the knowledge, attitudes and practices (KAP) survey, antimicrobial residue testing, multiple antibiotic resistance (MAR) index, plasmid curing procedure, influence of seawater on the bioactivity of antimicrobials, whole genome sequencing (WGS), ethics approvals and biorisk management has also been included. To our knowledge, this review provides the first comprehensive information as a guide for conducting AMU and AMR studies in shrimp aquaculture. In addition, it is suitable to be adapted for use in other animal farming sectors and helps pave the way for the implementation of systematic biosecurity strategies on farms worldwide.